Um modelo didático do gênero cordel: uma contribuição para o ensino e aprendizagem de gênero - Santos, Dalve Oliveira Batista (2014)
This research aims to identify the oral and written characteristics of cordel literature that may contribute to developing a didactic model aimed at the teaching and learning process of this genre. We understand as didactic model a descriptive object whose function is guiding school practices of production, by identifying the constitutive dimensions of genre and the selection of characteristics that may be taught. We chose to construct the didactic model because we think the study of textual genre with which we intend to work will provide greater knowledge about the genre concerned and it will allow constructing an educational material suitable to teach it. The construction of a didactic model is among the steps of a larger proposal to construct didactic sequences of genres, organized according to the relation between the genre, its teachable characteristics, and language capabilities (action, discursive, and linguistic-discursive capacity), which learners are expected to develop. Thus, to achieve the aim of this research, we seek to answer the following questions: a) What are the predominant characteristics of cordel works regarding the textual layers proposed by Bronckart? and b) What is the relationship between the levels of analysis and production and the language skills? The theoretical framework of this study is focused on the theoretical assumptions of sociodiscursive interactionism (BRONCKART, 1999) and the didactic issues of teaching genres (DOLZ & SCHNEUWLY, 2010), in addition to studies on cordel literature (ABREU, 2008; ACOPIARA, 2009; CAVALCANTI, 2008). The corpus consists of 4 works of the genre cordel written by authors from the state of Bahia, Brazil. Hence, the analytical procedures focus on the production conditions of these texts and their infrastructure in terms of organization, textualization mechanisms, and enunciative mechanisms. Therefore, analyzing cordel works leads us to conclude that the overall textual organization and the structuring of these texts depend on production conditions, specifically on representations made by the producer/enunciator regarding his production conditions